2013
DOI: 10.1146/annurev-micro-092412-155620
|View full text |Cite
|
Sign up to set email alerts
|

Wall Teichoic Acids of Gram-Positive Bacteria

Abstract: The peptidoglycan layers of many gram-positive bacteria are densely functionalized with anionic glycopolymers called wall teichoic acids (WTAs). These polymers play crucial roles in cell shape determination, regulation of cell division, and other fundamental aspects of gram-positive bacterial physiology. Additionally, WTAs are important in pathogenesis and play key roles in antibiotic resistance. We provide an overview of WTA structure and biosynthesis, review recent studies on the biological roles of these po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
855
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 786 publications
(872 citation statements)
references
References 154 publications
(256 reference statements)
14
855
0
3
Order By: Relevance
“…This may be due to the different stages of teichoic acid biosynthesis that are inhibited by tunicamycin and teixobactin. In the WTA biosynthesis pathway, the first two enzymes, TarO and TarA, are not essential under laboratory conditions, while most of the downstream factors are essential (37). The mechanism of this lethality may be due to accumulation of toxic intermediates or to depletion of cellular pools of cell wall precursors (37).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be due to the different stages of teichoic acid biosynthesis that are inhibited by tunicamycin and teixobactin. In the WTA biosynthesis pathway, the first two enzymes, TarO and TarA, are not essential under laboratory conditions, while most of the downstream factors are essential (37). The mechanism of this lethality may be due to accumulation of toxic intermediates or to depletion of cellular pools of cell wall precursors (37).…”
Section: Discussionmentioning
confidence: 99%
“…In the WTA biosynthesis pathway, the first two enzymes, TarO and TarA, are not essential under laboratory conditions, while most of the downstream factors are essential (37). The mechanism of this lethality may be due to accumulation of toxic intermediates or to depletion of cellular pools of cell wall precursors (37). Teixobactin is thought to inhibit the later steps of WTA biosynthesis by binding to lipid III outside the cell membrane (5).…”
Section: Discussionmentioning
confidence: 99%
“…Gram‐positive cell walls further contain carbohydrate‐based anionic polymers, primarily teichoic acids, which account for roughly half of the mass of the cell wall. Their physiological functions remain elusive but they play a major role in divalent cation binding (particularly Mg 2+ ) (Brown et al ., 2013; Neuhaus and Baddiley, 2003; Heckels et al ., 1977), they serve as scaffolds for a wide range of molecules and they regulate cell wall‐associated enzymes (Yamamoto et al ., 2008; Brown et al ., 2013). …”
Section: Introductionmentioning
confidence: 99%
“…Of these, three mutants had a transposon insertion within or directly upstream of genes involved in WTA biosynthesis. WTAs are surface-exposed anionic glycopolymers present in many Gram-positive species of bacteria, covalently bound to the peptidoglycan layer (Brown et al, 2013). Indeed WTA is the most abundant peptidoglycan bound The S. aureus RN4220 MIC of various aminoglycosides in the presence and absence of 1 mM SC is shown.…”
Section: Discussionmentioning
confidence: 99%
“…In TM39 the insertion was between tagO, which is associated with WTA biosynthesis (Soldo et al, 2002;Xia et al, 2010), and gdpS, the only conserved GGDEF domain protein identified thus far in Staphylococcus (Shang et al, 2009). Furthermore, the transposon insertion in TM26 was within tarJ, another gene involved in the WTA biosynthetic pathway (Brown et al, 2013). It should be noted, however, that although the insertion disrupted tarJ, this gene is duplicated in many S. aureus strains (Qian et al, 2006), and the locus SAOUHSC_00226 in the strain NCTC8325 most likely represents a second copy of tarJ.…”
Section: Regulatory Mutations In Wall Teichoic Acid Synthesis Stimulamentioning
confidence: 99%